Delivery of cytoplasmic and apoplastic effectors from Phytophthora infestans haustoria by distinct secretion pathways. Issue 1 (31st July 2017) - Wang, Shumei; Boevink, Petra C.; Welsh, Lydia; Zhang, Ruofang; Whisson, Stephen C.; Birch, Paul R. J.
Summary: The potato blight pathogen Phytophthora infestans secretes effector proteins that are delivered inside (cytoplasmic) or can act outside (apoplastic) plant cells to neutralize host immunity. Little is known about how and where effectors are secreted during infection, yet such knowledge is essential to understand and combat crop disease. We used transient Agrobacterium tumefaciens ‐mediated in planta expression, transformation of P. infestans with fluorescent protein fusions and confocal microscopy to investigate delivery of effectors to plant cells during infection. The cytoplasmic effector Pi04314, expressed as a monomeric red fluorescent protein (mRFP) fusion protein with a signal peptide to secrete it from plant cells, did not passively re‐enter the cells upon secretion. However, Pi04314‐mRFP expressed in P. infestans was translocated from haustoria, which form intimate interactions with plant cells, to accumulate at its sites of action in the host nucleus. The well‐characterized apoplastic effector EPIC1, a cysteine protease inhibitor, was also secreted from haustoria. EPIC1 secretion was inhibited by brefeldin A (BFA), demonstrating that it is delivered by conventional Golgi‐mediated secretion. By contrast, Pi04314 secretion was insensitive to BFA treatment, indicating that the cytoplasmic effector follows an alternative route for delivery into plant cells. Phytophthora infestans haustoria are thus sites for delivery of both apoplastic and cytoplasmic effectors during infection, following distinct secretion pathways. Abstract : See also the Commentary on this article by Van den Ackerveken, 216 : 8–10 .